Examining the Mediating Role Supply Chain Identity Salience in the Relationship between Its Antecedents and Supply Chain Social Capital: A Case of Thai Manufacturing Firms - Suteerachai, Boonsri; Toopgajank, Sriparinya; Wongwiwat, Piyada; Aramrueang, Pannamas (International Journal of Supply Chain Management, 2019)
The main reason behind carrying out the current study is to examine the mediating role supply chain identity salience in the relationship between its antecedents and supply chain social capital. In this study a new paradigm is presented by supply chain management (SCM) where a systems approach is adopted by firms to manage the supply chain not as a set of fragments but as s single entity, having a sole purpose of synchronizing and adjusting the supply chain activities of partnering firms to develop greater customer value as compared to other supply chain. It is proposed in this study that successful functioning of managed supply chain only takes place when supply chain partners that are involved in crucial relationships actively share a feeling of identity or belonging with the supply chain. Such strong sense of identity plays an essential role in a context of the managed supply chain, as the supply chain management majorly depends upon the cooperation of resultant voluntary independent organizations and social processes and not on the financial or legal ownership. The study has used the SEM-PLS to achieve the objectives of the current study. The study is carried out on the sample of manufacturing firms operating in Thailand. This study presents a detailed view of social processes with respect to SCM context, with the purpose of indicating the contributory role played by supply chain identity salience in the social capital formation.